Assessing content and bias in South African Permo-Triassic Karoo tetrapod fossil collections - Nicolas, Merrill; Rubidge, Bruce S. (Bernard price Institute for Palaeontological Research, University of the Witwatersrand, 2009)
A standardized taxonomic database as well as a Geographical Information System (GIS) database of all fossil tetrapods collected from the Permo-Triassic Beaufort Group rocks of South Africa has been compiled from a number of South African museum catalogues. The data capture required rigorous evaluation of the accuracy of the original records and the degree of collecting bias. The outcome of this evaluation endorsed the accuracy of the two databases and showed no significant degree of collecting bias. This standardized database, now linked to a new GIS-based database, will be a valuable resource to scientists researching Permo-Triassic biodiversity and faunal distribution patterns.
Keywords: digitized data; fossil database; Beaufort Group